PENGARUH GREEN MARKETING TOOL'S TERHADAP PERILAKU PEMBELIAN KONSUMEN - Prastiyo, Yuni (E-Jurnal Manajemen; Vol 5 No 6 (2016), 2016)
This study aims to determine the extent of the influence of green marketing tool and the variables which most influence on consumer buying behavior. The location study was conducted in the city of Denpasar. The number of samples used by 100 respondents using the technique of Non probabilty sampling, particularly purposive sampling. The data collected is processed using multiple linear regression techniques. Results show any variables tested have valid and reliable, and has met the test of classical assumptions. Based on the results of the analysis showed that green marketing tools (eco-labeling, eco-brand, and eviromental advertisment) gives significant positive effect on consumer buying behavior (consumers'purchase behavior). Among the independent variable is the most dominant effect is eco-brand.
Keywords: consumer buying behavior (consumers' purchase behavior), eco-label, eco-brand, eviromental advertisment